Perancangan Teknologi Fasilitas Kerja dengan Metode Rapid Upper Limb Assessment (RULA) dan Berdasarkan Antropometri Tubuh pada Pengrajin Daun Nipah - Bayu Febrilliandika; Ageng Aprisandi; Nurhasanah Ritonga (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
Nipah craftsmen in Terjun Village, Medan Marelan District, in doing their work, tend not to pay attention to ergonomic concepts related to body posture. The aim of this research is to produce a work facility design that can help Nipah craftsmen do their work with a more ergonomic body posture. The method used in this research is to use RULA measurements and body anthropometry. Based on the RULA score, the posture of the Nipah craftsman is given a score of 5 or falls into the posture category that needs immediate change investigation. The output of this research is the design of tools to improve the posture of Nipah leaf workers. The dimensions of the work facility design are determined by the anthropometric data of the palm leaf craftsmen using the 95th percentile. The results obtained are Elbow height sitting (EHS)) of 25.71, Popliteal height (PH)) of 46.43, Elbow breadth sitting (EBS) of 46.73, Hip width (HW) of 37.73, and Shoulder height sitting (SHS) of 68,53.